EVALUATION OF ROAD GEOMETRY TO TOURISM AREAS (CASE STUDY: EAST RING ROAD - JATIGEDE DAM, SUMEDANG - INDONESIA) - Nina Rifka Puspitasari; Mulia Pamadi; Adinda Fajarika (Fakultas Teknik Sipil dan Perencanaan, 2024)
Road geometry design is a method of planning roads geometrically or involving the computation a angles through a process. For roads geometric design, it is necessary to assess the suitability of design criteria with applicable guidelines, namely the Road Geometric Design Guidelines. Therefore, this study will conduct a geometric design assessment of application of the existing road geometric design of the Jatigede East Ring Roads, and adjust it to the